Télétravail, Famille, Patrie - Cécile GIRARDIN (E-REA)
“Télétravail, Famille, Patrie” chronicles daily life under the lockdown that was imposed in March 2020, from the perspective of a single mother of three small children. Written in a sarcastic style, it focuses on the petty annoyances of the “new normal”, evoking daily chores through realistic dialogues and accurate descriptions of material life (the challenge of group outing, grocery shopping, not having an internet connection, home schooling, and so on).